The Johns Hopkins Guide to Diabetes : For Patients and Families - Saudek, Christopher D. (Book collections on Project MUSE., 2014)
A comprehensive and easy-to-read guide to diabetes. The authors will help you understand the disease, and work with your care team to maintain good health.